STRATEGI KOMUNIKASI PEMASARAN UNTUK MENINGKATKAN KEPUASAN NASABAH TERHADAP PELAYANAN DAN PRODUK KREDIT BANK KALSEL - Rizka Amalia Putri; Muhammad Yunus Jarmie; M.S. Sailillah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
Based on human awarness that improve to be more clever and smarter to choose the best product and quality, Kalsel Bank has a strategic plan for it's employee to improve customer's satisfication. The strategic plan applied from service to all of the selling products. Specially it's credit product that usually help customers in needed with special offer.The purpose of study marketing communication to increas customer's satisfication is to knowing the communication strategy of Kalsel Bank to be trusted by customers, to get the data of customer's satisfication of it's service, and knowing factors that could influence customer's satisfication for it's service and credit products. Subjects of the study are six men and six women around thirty one to forty years old. It separated by two steps as pre research and extention research with interview as instrument and using triangulasi method.The result of this study that has gotten by reducted the data, compared the data with all communication theory that been used as persuation communication, interpersonal communication, and non verbal communication, and also compared with the datas on previous study. SWOT analyse being used for the image of Kalsel Bank.The result of this study is a superfine service that stated in Superfine Culture in Kalsel Bank and must be applied to all of credit service employee so, all of the customers are able to get superfine service and the best product, this strategy is able to create loyal customer who feel satisfy. Based on factors that have a role as mastery the persuasif communication technique of Kalsel Bank's employee, to honor it's mission as best quality service provider, cheap interest on Multiguna credit product.